Pengaruh Penggunaan Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Peserta Didik - Oktaviyana, Wida Nurul; Nurlatifah, Nurlatifah; Sari, Eka Atika (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
The purpose of this study was to determine the effect of the Problem Based Learning model on student learning outcomes in learning IPAS force material in class IV SDN 3 Bojongmengger. This research is a quantitative research experiment in the form of Pre-experimental Design using One Group Pretest-Posttest Design. Data collection techniques using tests in the form of multiple choice questions as many as 20 questions. The data analysis technique used is descriptive statistical data analysis and inferential statistical data analysis / prerequisite test with the help of using the SPSS 26 program. Based on the calculation, the pretest results obtained before the treatment using the Problem Based Learning learning model with a total of 15 students, many of whom were below KKTP. After the treatment using the Problem Based Learning learning model with a total of 15 students, many students' learning outcomes were above KKTP. Based on hypothesis testing, the test results are 0.001 <0.5, so the Ho hypothesis is rejected and Ha is accepted, it can be concluded that the Problem Based Learning learning model has an effect on student learning outcomes in learning IPAS force material at SDN 3 Bojongmengger.